Analisa Pengaruh Penerapan Absensi Melalui Disiplin Kerja Sebagai Variabel Intervening Terhadap Kinerja Pegawai Penyuluh Keluarga Berencana (Studi Kasus Dinas P3APPKB Kabupaten Blitar) - Aang Dwi Saputro; Arisyahidin Arisyahidin; Deby Satyo Rusandy (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
The purpose of this study was to determine the effect of implementing absenteeism on employee discipline and the performance of family planning extension workers at the P3APPKB Office of Blitar Regency partially, to determine the effect of work discipline on the performance of family planning extension officers at the P3APPKB Office of Blitar Regency and to determine the effect of implementing absenteeism through discipline. Work as an Intervening Variable on the Performance of Family Planning Extension Officers at the P3APPKB Office of Blitar Regency. The population in this study were all employees of the Blitar Regency P3APPKB Office, totaling 79 employees. Based on the calculation of the number of samples using the slovin formula, a sample of 66 respondents was obtained. The data analysis technique used in this research is SmartPLS-SEM. The results of the study show that 1) Absenteeism has an effect on the Discipline of Family Planning Extension Officers at the P3APPKB Office of Blitar Regency; 2) Absence does not affect the performance of Family Planning Extension Officers at the P3APPKB Office of Blitar Regency; 3) Work Discipline has an impact on the Performance of Family Planning Extension Officers at the P3APPKB Office of Blitar Regency; 4) Application of Absence through Work Discipline as an Intervening variable affects the Performance of Family Planning Extension Employees at the P3APPKB Office of Blitar Regency.